Morphometric and genetic variations of the Poison Frog (Odorrana hosii Boulenger 1891) in Jatimulyo, Kulon Progo, Yogyakarta using microsatellite markers - Enggar Pramesti Galuh; Suwartiningsih Nurul (BIO Web of Conferences)
One of the abundant amphibian species in Indonesia is Odorrana hosii. This species exhibits a wide distribution range and varies in morphometric and genetic characteristics. However, the morphometric and genetic variations of Odorrana hosii populations in Jatimulyo area of Kulon Progo, Yogyakarta, have not been previously studied. This research aims to investigate the morphometric and genetic variations of three populations: Sungai Mudal, Kembang Soka, and Kedung Pedut. Sampling was conducted in Jatimulyo ecotourism area, and morphometric measurements were taken from individual Odorrana hosii specimens. Genetic analysis was performed using Polymerase Chain Reaction (PCR) with microsatellite markers Rnh-9 and Rnh-13 at the Molecular Biology Laboratory, Ahmad Dahlan University. Morphometric analysis involved 27 characters observed in 9 male and 9 female individuals, while genetic analysis focused on amplified loci. Kruskall-Wallis analysis was used to compare interpopulation morphometric data, revealing four distinguishing characters with P<0.05. The results showed that head length (HL), nostril distance (IND), thigh length (TL), and total leg length (HLL) were longest in males from Kembang Soka population and shortest in males from Kedung Pedut population. Genetic variation analysis indicated the highest DNA polymorphism in Kembang Soka population (90.90%), followed by Kedung Pedut (60%) and Sungai Mudal (50%). Overall, Kembang Soka population exhibited the most significant morphometric and genetic variations.